Role of mental health practitioner in infertility clinics: A review on past, present and future directions - Ansha Patel; P S. V. N. Sharma; Pratap Kumar (Wolters Kluwer Medknow Publications, 2018)
A large body of literature has emerged over the past four decades which highlights the need to address emotional needs in infertility and integrates psychological services within routine fertility care. Evidenced-based guidelines in most countries propagate that the mental health expert (MHP) plays a vital role as a team member in reducing the impact of infertility on the lives of patients, across all stages of treatment. In accordance with these global developments, inclusion of psychosocial care in fertility treatments is an upcoming trend in our nation. This review article brings forth the traditional role of MHP in infertility, compares patient-centered care with counseling, and elaborates on the guidelines on determinants of patient needs and suitability for structured psychological interventions. It also highlights the evidence-based studies on the application of psychotherapy in infertility.